Papua New Guinea food price bulletin: April 2022 - International Food Policy Research Institute; Schmidt, Emily; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2022)
The per kilo sweet potato (2020 real) price in Port Moresby and Lae in the 1st quarter of 2022 were nearly double the per kilo sweet potato price of the 1st quarter of 2021. The price of cassava and taro held stable in quarter 1 with minimal price changes between January and April across all markets. While, globally, commodity food prices are rising due to supply chain issues and concerns over the Russia-Ukraine conflict, thus far rice prices in PNG remain stable. Vitamin dense fresh vegetables are more costly than staple foods in PNG. However, in Goroka, Mt. Hagen, and Lae, the kg prices of broccoli, carrot and cabbage in the first quarter of 2022 were comparable to taro and cooking banana.